2002
DOI: 10.1046/j.1471-4159.2002.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cdk5 and its activators in NT2 cells during neuronal differentiation

Abstract: We have recently developed a rapid protocol involving NT2 cell aggregation and treatment with retinoic acid (RA) to produce terminally differentiated CNS neurons. As a first step to explore the functional roles of cell-cycle regulatory proteins in the process of neuronal differentiation, the expression profiles of cyclin-dependent kinases (Cdks) and their regulators were examined in NT2 cells following treatment with RA. One of the Cdks, Cdk5, has been demonstrated to affect the process of neuronal differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 49 publications
1
23
0
1
Order By: Relevance
“…Interestingly, the pattern observed is the exact opposite of the CDK5 activity pattern, suggesting a potential link between the two events. Our results confirm those found by Fu et al [20] during NT2 differentiation using a cell aggregation method [21]. Here, we found that the pattern of activity and expression of CDKs is comparable whether the aggregation or the plating method is used.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the pattern observed is the exact opposite of the CDK5 activity pattern, suggesting a potential link between the two events. Our results confirm those found by Fu et al [20] during NT2 differentiation using a cell aggregation method [21]. Here, we found that the pattern of activity and expression of CDKs is comparable whether the aggregation or the plating method is used.…”
Section: Discussionsupporting
confidence: 92%
“…In situ, in differentiated neurons, GSK-3 clearly seems to have a role in tau phosphorylation as was shown by inhibition of GSK-3 with LiCl (Hong et al, 1997;Muñoz-Montaño et al, 1997). Of the cyclin-dependent kinases in differentiated neurons, cdc2, which is activated in dividing cells (Meyerson et al, 1992) is most probably of less importance than cdk5, the activity of which is increased in differentiating neurons (Fu et al, 2002). However, relatively little is known about tau phosphorylation by cdk5.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were maintained in Dulbecco's modified Eagle medium (DMEM, Life Technologies, Rockville, MD, USA) supplemented with 10% fetal bovine serum, 50 U/ml penicillin, and 100 mg/ml streptomycin, at 371C, in a humidified atmosphere of 7.5% CO 2 . At 80% confluence, cells were exposed in DMEM containing 1% FBS to 2.5% EtOH, 25 mg/ml cycloheximide (CHX, dissolved in EtOH), or 20 mM CPT (dissolved in DMSO), for 18 h. For the kinetic study of cells exposed to 20 mM CPT, cells were collected at 0, 3,6,8,12,15, and 18 h. To block calpain activation induced by CPT in both C8 and A9 cells, two calpain inhibitors, 10 mM CS or 10 mM PD, were coadministered with CPT and cells were incubated for 18 h. To inhibit Cdk5 activation, cells were treated with roscovitine alone or in combination with CPT for 18 h.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…[2][3][4][5][6] Unlike other cell cycle-promoting members of Cdk family, Cdk5 kinase primarily modulates neuroskeletal dynamics in postmitotic neurons. 3,7,8 Cdk5 plays an essential role in both developing and adult neurons, including neuronal migration, 9,10 axon guidance, 11 neurite outgrowth, 7 dynamics of synaptic structure, [12][13][14] neurotransmission, 15,16 and neuronal secretion. 17 Cdk5 null mice suffer perinatal mortality, with severe defects in neuronal migration and laminar configuration in the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%